Stress appraisals and resilience as predictors of psychological distress among individuals experiencing involuntary job loss in Malaysia - Zulkifly, Nurul Izzati Asyikin; Hussin, Ruhaya (2018)
This study aims to investigate whether stress appraisals (i.e., positive and negative perception of stress) and resilience among individuals experiencing involuntary job loss in Malaysia predict their psychological distress. It was hypothesized that both stress appraisals and resilience predict psychological distress. A cross-sectional survey design was used, in which data was collected by using self-report questionnaires. A total of 229 participants who were laid off and unemployed within one month to three years were approached by using snowball technique. Results from hierarchical multiple regression indicates that stress appraisals and resilience predict psychological distress, F (6, 210) = 44.85, p < .001. The results support stress as a contributor to increased psychological distress and resilience as a predictor predicts of reduced psychological distress. This paper discusses the research findings within Malaysian context, as well as highlighting the limitation of the present study and recommendations for future research.